The effect of dust deposition on the morphology and physiology of tree foliage - Soheili, Forough; Woodward, Stephan; Abdul-Hamid, Hazandy; Naji, Hamid Reza (Springer, 2023)
Due to climate change, natural hazards have increased around the world. One of these hazards is dust storms, which cause problems for people in arid and semi-arid regions. The inherent properties of dust particles can affect the atmospheric, oceanic, and continental climate systems. The leaf surface of plants constantly absorbs particulate matter, which helps to improve air quality. However, plants can also be affected by the accumulation of particulate matter. This article reviews research on how dust affects the morphological, physiological, and biochemical properties of tree leaves. The ability of vegetation to capture and retain atmospheric particulate matter depends directly on the interactions between particulate matter and plant surfaces. Atmospheric dust places additional stress on plants because they often respond to atmospheric pollution in a manner similar to drought and other environmental stresses. However, the extent to which leaf properties are affected by particulate matter is still controversial. Dust impacts on morpho-anatomical characteristics of the leaf. Young leaves with soft tissues are more vulnerable than rigid leaves. High-trichome leaf can keep more dust causing necrosis and chlorosis on the leaf. Fine particles with sizes of about 2.5 μm can penetrate inside the leaves’ tissues through the stomata leading to the degradation of chloroplast and pigments. With reduction in plant photosynthesis, a change will happen in wood cellular features by affecting the cambium. The lack of basic information on changes in plant structure, as well as the role dust plays in life cycles, is a challenge for developing management protocols and research plans on this problem.